Tactical rules for ambush - Ciocan, Maria-Alexandra (Eximia, 2023)
The police plays a significant role in the institutional organization of a State, holding the difficult but also delicate mission of maintaining order and public safety, defending citizens' rights and liberties. Because from the beginning, among the needs of the first existing communities was also the need for safety, although over the years, this aspect has been addressed in several ways, this need has always been associated with the duties of the police. In specialized literature, literary critics approached this theme, as it is the essential activity for society, in order to maintain order and public safety. There are also regulations, such as the Constitution of Romania, which deals with stalking from the perspective of the obligations of specialized institutions. Reading several articles and focusing on the tactical rules, I learned that over the years in the practical activity of the police it often happens that they pay "tribute" due to non-compliance with the tactical rules, or the carelessness with which these were treated rules, thus paying with his life. In this sense, in the first chapter, the work aims to present the tactical rules regarding the execution of the ambush, thus aiming at the insufficiency of the works dealing with this subject, a better knowledge of the tactical rules, at least from the point of view of the execution of the ambush.